Dynamic Response Analysis and Verification of Shipboard Structure Using Composite Materials and Resilient Mounts - Lee, Jae-Eun; Kwak, Yeong-Chan; Jeong, Eui-Bong; Jung, Hwa-Young; Park, Sung-Woo; Jo, Hyun-Wook (International journal of precision engineering and manufacturing, 2022)
Equipment testing and FEM analysis are common engineering problem solving methods used by engineers. However, in the problem-solving method by FEM analysis, the engineers should use an appropriate analysis solver, assume boundary conditions, and use the correct material properties to increase the reliability of finite element (FEM) analysis. In the case of solvers, the efforts of companies developing commercial analysis programs have greatly increased the reliability of the analysis solver, so engineers can achieve the reliability of the solver simply by selecting the correct solver for the engineering problem. However, the boundary conditions and material properties are usually based on the assumptions and experience of the engineer, but if the equipment becomes complex, uncertainty accumulates and the reliability of the analysis at the system level is greatly reduced. In particular, since there is no information when designing a product for the first time, it is difficult to expect the reliability of FEM modeling without applying an appropriate method. In the shipboard structure studied in this paper, it is difficult to predict the structural response at the system level due to the accumulation of uncertainty because the resilient mount, antenna pedestal, and radome are intricately connected and the isotropic material and anisotropic material are combined. In this paper, we applied a stepwise verification method to increase the reliability of FEM analysis of the shipboard structure. We performed experiments and FEM analysis on the shipboard structure using the method presented in this paper and found that the response of the natural frequency was consistent within about 1%. In addition, the acceleration response for all frequencies was consistent within 5%.